Administration of artinm lectin reduces the severity of the acute phase infection with Trypanosoma cruzi. Issue 5 (25th January 2021) - Miguel, Camila Botelho; da silva, Thiago Aparecido; Rodrigues, Wellington Francisco; Oliveira‐Brito, Patrícia Kellen Martins; Roque‐Barreira, Maria Cristina; Lazo‐Chica, Javier Emílio
Abstract: The acute phase of experimental Trypanosoma cruzi infection is associated with a strong inflammatory reaction, physiological changes, amastigote nests in tissues, and hematological alterations. ArtinM, a lectin extracted from Artocarpus heterophyllus seeds, is a homotetramer exhibiting immunomodulatory properties that promotes Th1 immune responses against intracellular pathogens, including the induction of neutrophil migration and increase in IL‐12 production. This study aimed to evaluate the effects of ArtinM on experimental Chagas disease in mice. We evaluated mouse survival curves, parasitemia, hematological parameters including quantification of inflammatory infiltrates, and amastigote nests in cardiac tissue during infection. The results showed a reduced number of parasites in the blood, an increase in animal survival, improvements in hematological parameters, and decrease in inflammatory infiltrates and amastigote nests in the group treated with ArtinM. Collectively, these data suggest that the administration of ArtinM can lower the number of parasites in peak parasitemia caused by the Colombian strain of T. cruzi and can increase survival of infected mice. The observed reduction in cardiac tissue injury may be due to fewer T. cruzi amastigote nests and lower levels of inflammatory infiltrates. This study highlights the need for further investigation into the use of ArtinM as a potential alternative therapeutic for treating Chagas disease.